Angiotensin-II type 2 receptor-mediated renoprotection is independent of receptor Mas in obese Zucker rats fed high-sodium diet - Patel, Sanket N.; Kulkarni, Kalyani; Faisal, Tahmid; Hussain, Tahir (Frontiers in Pharmacology, 2024)
The consumption of high-sodium diet (HSD) is injurious and known to elevate blood pressure (BP), especially in obesity. The acute infusion studies depict functional interdependency between angiotensin-II type 2 receptor (AT2R) and receptor Mas (MasR). Hence, we hypothesize that subacute blockade of MasR should reverse AT2Rmediated renoprotection in obese Zucker rats (OZR). Male OZRs were fed HSD (for 14 days) and treated with the AT2R agonist C21 (100 ng/min) without or with MasR antagonist A779 (1000 ng/min). The indices of oxidative stress, proteinuria, kidney injury, and BP were measured before and after along with the terminal measurements of an array of inflammatory and kidney injury markers. The HSD significantly decreased estimated glomerular filtration rate and urinary osmolality, and increased thirst, diuresis, natriuresis, kaliuresis, plasma creatinine, urinary excretion of H2O2, proteinuria, renal expression and urinary excretion of kidney injury markers (NGAL, KIM-1), and BP indices.The HSD feeding showed early changes in renal expression of CRP, ICAM-1, and galectin-1. The C21 treatment prevented these pathological changes. The MasR antagonist A779 attenuated C21-mediated effects on the urinary excretion and renal expression of NGAL, and oxidative stress in the absence of inflammation and BP changes. Overall, we conclude that the subacute functional interactions between AT2R and MasR are weak or transient and that beneficial effects of AT2R activation are independent of MasR blockade in the kidney of male obese rats fed HSD.